Thermal stabilization of metal matrix nanocomposites by nanocarbon reinforcements. (September 2020) - Bachmaier, A.; Katzensteiner, A.; Wurster, S.; Aristizabal, K.; Suarez, S.; Pippan, R.
Abstract: Metal matrix composites reinforced by nanocarbon materials, such as carbon nanotubes or nanodiamonds, are very promising materials for a large number of functional and structural applications. Carbon nanotubes and nanodiamonds-reinforced metal matrix nanocomposites with different concentrations of the carbon phase were processed by high-pressure torsion deformation and the evolving nanostructures were thoroughly analyzed by electron microscopy. Particular emphasis is placed on the thermal stability of the nanocarbon reinforced metal matrix composites, which is less influenced by the amount of added nanocarbon reinforcements than by the nanocarbon reinforcement type and its distribution in the metal matrix. Graphical abstract: Image, graphical abstract